Comparison of screening CEDM and MRI for women at increased risk for breast cancer: A pilot study. Issue 97 (December 2017) - Jochelson, Maxine S.; Pinker, Katja; Dershaw, D. David; Hughes, Mary; Gibbons, Girard F.; Rahbar, Kareem; Robson, Mark E.; Mangino, Debra A.; Goldman, Debra; Moskowitz, Chaya S.; Morris, Elizabeth A.; Sung, Janice S.
Highlights: Women at increased breast cancer risk benefit from supplemental imaging. Contrast mammography detects cancers not seen on routine mammography. PPV3 of contrast mammography is similar to MRI. Abstract: Objectives: Contrast enhanced digital mammography (CEDM) is a new breast imaging technology increasingly used in the diagnostic setting but its utility in the pure screening setting has not been reported. The goal of this pilot study is to prospectively compare screening CEDM to breast MRI in women with an increased risk for breast cancer. Methods: In this IRB-approved HIPAA-compliant study, 318 women at increased breast cancer risk were consented (December 2012–May 2015) to undergo CEDM in addition to their scheduled MRI. CEDM was performed within 30 days of screening MRI. CEDM was interpreted blinded to MRI. The reference standard was defined as a combination of pathology and 2-year imaging follow-up. Results: Data from 307/318 patients were evaluable. Three cancers (two invasive cancers, one ductal carcinoma in situ) were detected at first round screening: MRI detected all three and CEDM detected the two invasive cancers. None of the three cancers was seen on the low energy mammograms which are comparable to conventional mammography. At 2 year imaging follow up, there were 5 additional screen detected cancers and no palpable cancers. The positive predictive value 3 (PPV3 ) for CEDM was 15% (2/13, 95% CI: 2–45%) and 14% for MRI (3/21, 95% CI: 3–36%). The specificity of CEDM and MRI were 94.7% and 94.1% respectively. Conclusions: Both CEDM and MRI detected additional cancers not seen on conventional mammography, primarily invasive cancers. Our pilot data suggest that CEDM could be valuable as a supplemental imaging exam for women at increased risk for breast cancer who do not meet the criteria for MRI or for whom access to MRI is limited. Validation in larger multi institutional trials is warranted.